Scheduling preemptable jobs on identical processors under varying availability of an additional continuous resource - Różycki, Rafał; Waligóra, Grzegorz; Węglarz, Jan (1947- ) (Zielona Góra: Uniwersytet Zielonogórski)
Their processing speeds depend on the amounts of a continuous, renewable resource allocated to jobs at a time. Jobs are scheduled on parallel, identical machines, with the criterion of minimization of the schedule length. Since two categories of resources occur in the problem: discrete (set of machines) and continuous, it is generally called a discrete-continuous scheduling problem. The model studied in this paper allows the total available amount of the continuous resource to vary over time, which is a practically important generalization that has not been considered yet for discrete-continuous scheduling problems.
Keywords: machine scheduling; preemptable jobs; continuous resource; makespan; mathematical programming